Efficacy and safety of dual blockade of the renin-angiotensin system: meta-analysis of randomised trials - Makani, Harikrishna (BMJ Publishing Group Ltd., 2013)
Objective To compare the long term efficacy and adverse events of dual blockade of the renin-angiotensin system with monotherapy. Design Systematic review and meta-analysis. Data sources PubMed, Embase, and the Cochrane central register of controlled trials, January 1990 to August 2012. Study selection Randomised controlled trials comparing dual blockers of the renin-angiotensin system with monotherapy, reporting data on either long term efficacy (≥1 year) or safety events (≥4 weeks), and with a sample size of at least 50. Analysis was stratified by trials with patients with heart failure versus patients without heart failure. Results 33 randomised controlled trials with 68 405 patients (mean age 61 years, 71% men) and mean duration of 52 weeks were included. Dual blockade of the renin-angiotensin system was not associated with any significant benefit for all cause mortality (relative risk 0.97, 95% confidence interval 0.89 to 1.06) and cardiovascular mortality (0.96, 0.88 to 1.05) compared with monotherapy. Compared with monotherapy, dual therapy was associated with an 18% reduction in admissions to hospital for heart failure (0.82, 0.74 to 0.92). However, compared with monotherapy, dual therapy was associated with a 55% increase in the risk of hyperkalaemia (P<0.001), a 66% increase in the risk of hypotension (P<0.001), a 41% increase in the risk of renal failure (P=0.01), and a 27% increase in the risk of withdrawal owing to adverse events (P<0.001). Efficacy and safety results were consistent in cohorts with and without heart failure when dual therapy was compared with monotherapy except for all cause mortality, which was higher in the cohort without heart failure (P=0.04 v P=0.15), and renal failure was significantly higher in the cohort with heart failure (P<0.001 v P=0.79). Conclusion Although dual blockade of the renin-angiotensin system may have seemingly beneficial effects on certain surrogate endpoints, it failed to reduce mortality and was associated with an excessive risk of adverse events such as hyperkalaemia, hypotension, and renal failure compared with monotherapy. The risk to benefit ratio argues against the use of dual therapy.